Criminal Code in Environmental Perspective - Hasanal Mulkan (International Journal of Global Sustainable Research, 2023)
Environmental law in the field of legal science is one of the most strategic fields of legal science because environmental law has many aspects, namely administrative law, criminal law and civil law. The Indonesian Criminal Code (KUHP) does not specifically regulate environmental law explicitly. However, there are several articles in the Criminal Code that can relate to environmental violations. Environmental crimes are regulated in Chapter XV, which consists of 23 articles, starting from Article 97 to Article 120 UUPPLH. In the Criminal Code, there are several articles relating to types of environmental violations that can be discussed, such as air pollution, water pollution, hazardous waste disposal, forest destruction and illegal hunting. Collaboration between government, society and the private sector has an important role in environmental law. Synergy between these three parties is needed to achieve effective and sustainable environmental protection.